Les usages scolaires du «Roi grenouille»: le cas des manuels scolaires de l'école et du collège (1995-2016) - Boutevin, Christine Paulette; Richard-Principalli, Patricia (Ondina - Ondine, 2018)
«The frog King», as a tale, belongs to the heritage literature that school and the college give as an object of study, both in the lists of literary works of reference of the primary school and in the Programs Of the college. The article relies on a corpus of 96 primary and sixth textbooks published between 1995 and 2016 to observe how the school edition took over «the frog King». It shows and explains the weak representation of this Grimm tale and the important presence of the diversions to which this work gave rise in these textbooks. More specifically, the analysis of two textbooks proposing an integral version of «the frog King» makes it possible to understand the didactic issues assigned to his reading.Keywords : The frog King, Manual, school use, Secondary Semiotic Objects, hijacked tale